One-step chemically vapor deposited hybrid 1T-MoS2/2H-MoS2 heterostructures towards methylene blue photodegradation - D. Mouloua; M. Lejeune; N.S. Rajput; K. Kaja; M. El Marssi; M.A. El Khakani; M. Jouiad (Ultrasonics Sonochemistry, 2023)
The photocatalytic degradation of methylene blue is a straightforward and cost-effective solution for water decontamination. Although many materials have been reported so far for this purpose, the proposed solutions inflicted high fabrication costs and low efficiencies. Here, we report on the synthesis of tetragonal (1T) and hexagonal (2H) mixed molybdenum disulfide (MoS2) heterostructures for an improved photocatalytic degradation efficiency by means of a single-step chemical vapor deposition (CVD) technique. We demonstrate that the 1T-MoS2/2H-MoS2 heterostructures exhibited a narrow bandgap ∼ 1.7 eV, and a very low reflectance (<5%) under visible-light, owing to their particular vertical micro-flower-like structure. We exfoliated the CVD-synthesised 1T-MoS2/2H-MoS2 films to assess their photodegradation properties towards the standard methylene blue dye. Our results showed that the photo-degradation rate-constant of the 1T-MoS2/2H-MoS2 heterostructures is much greater under UV excitation (i.e., 12.5 × 10−3 min−1) than under visible light illumination (i.e., 9.2 × 10−3 min−1). Our findings suggested that the intermixing of the conductive 1T-MoS2 with the semi-conducting 2H-MoS2 phases favors the photogeneration of electron-hole pairs. More importantly, it promotes a higher efficient charge transfer, which accelerates the methylene blue photodegradation process.